2010
DOI: 10.1007/s12282-009-0186-9
|View full text |Cite
|
Sign up to set email alerts
|

Radiofrequency ablation as local therapy for early breast carcinomas

Abstract: RF ablation is a safe and promising minimally invasive treatment for small breast carcinomas with pathological tumor size ≤ 2 cm in diameter and without EIC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(40 citation statements)
references
References 17 publications
0
39
0
1
Order By: Relevance
“…A total of 63 articles matched the selection criteria. The 63 articles included 16 feasibility studies [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28], 12 phase I studies [29][30][31][32][33][34][35][36][37][38][39][40], nine phase II studies [41][42][43][44][45][46][47][48][49], three comparative studies [50][51][52], one retrospective study [53], and four randomised controlled trials [54][55][56]. In 18 studies the type of study was not reported [8,[57][58][59][60][61][62][63][64]…”
Section: Selected Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 63 articles matched the selection criteria. The 63 articles included 16 feasibility studies [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28], 12 phase I studies [29][30][31][32][33][34][35][36][37][38][39][40], nine phase II studies [41][42][43][44][45][46][47][48][49], three comparative studies [50][51][52], one retrospective study [53], and four randomised controlled trials [54][55][56]. In 18 studies the type of study was not reported [8,[57][58][59][60][61][62][63][64]…”
Section: Selected Studiesmentioning
confidence: 99%
“…In five studies [21,24,49,59,63], patients withdrew from the study during or after treatment and in another six studies [15,26,44,48,49,72] patients withdrew before the start of the treatment. The overall STROBE score ranged from four to seven (mean…”
Section: Quality Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently Takayuki [22] et al treated 49 patients, aged 36 -82 years and tumor size ≤3.0 cm in diameter (range 0.5-3.0 cm) on US examination. Under US guidance, the 17-gauge ValleylabTM RF Ablation System with Cool-tip TM Technology (Covidien, Energy-Based Devices, Interventional Oncology, Boulder, CO) was inserted in the center of the tumor.…”
Section: Medina Et Al (2008)mentioning
confidence: 99%
“…A FEM model was used in this work because it can provide users with quick, accurate solutions to multiple systems of differential equations and therefore, they are well suited to solve heat transfer problems like ablation [27]. Numerous MWA antenna designs specifically targeted for MWA cardiac and hepatic applications have been reported [20][21][22][23][24], but they have not been used to treat breast cancer. These designs have been focused largely on thin, coaxial-based interstitial antennas [28], which are minimally invasive and capable of delivering a large amount of electromagnetic power.…”
Section: Advanced Computer Modeling In Breast Cancer Hyperthermia Trementioning
confidence: 99%